Exercise Training Increases Parietal Lobe Cerebral Blood Flow in Chronic Stroke: An Observational Study - Robertson, Andrew D.; Marzolini, Susan; Middleton, Laura E.; Basile, Vincenzo S.; Oh, Paul I.; MacIntosh, Bradley J. (Frontiers in Aging Neuroscience, 2017)
Exercise is increasingly recommended as an essential component of stroke rehabilitation, yet uncertainty remains with respect to its direct effect on the cerebral vasculature. The current study first demonstrated the repeatability of pseudo-continuous arterial spin labeling (ASL) magnetic resonance imaging in older adults with stroke, and then investigated the change in cerebrovascular function following a 6-month cardiovascular rehabilitation program. In the repeatability study, 12 participants at least 3 months post-stroke underwent 2 ASL imaging scans 1 month apart. In the prospective observational study, eight individuals underwent ASL imaging and aerobic fitness testing before and after a 6-month cardiovascular rehabilitation program. Cerebral blood flow (CBF) and the spatial coefficient of variation of CBF (sCoV) were quantified to characterize tissue-level perfusion and large cerebral artery transit time properties, respectively. Group mean interscan differences for both grey matter CBF and sCoV metrics were less than 1% of the single scan values, suggesting good repeatability in individuals with chronic stroke. In the observational study, grey matter CBF increased after training (baseline: 40±13 vs. 6-month: 46±12 ml/100g/min, P=0.036). The greatest change occurred in the parietal lobe (+18±12%). Grey matter sCoV, however, did not change following training (P=0.31). This study provides preliminary evidence that exercise-based rehabilitation in chronic stroke enhances tissue-level perfusion, without changing the relative hemodynamic properties of the large cerebral arteries.